Michael Handelsman, pionero en los estudios de la literatura afroecuatoriana (Tributo) - Balladares, María Auxiliadora (2019)
This article reviews Michael Handelsman’s contributions to studies on Afro-Ecuadorian Literature. Handelsman is a pioneer in the field, and his book published in 1999, Lo afro y la plurinacionalidad: el caso ecuatoriano visto desde su literatura, is the most outstanding contribution and the most careful and profound study regarding the importance of observing, in the turn of the century, the contributions made by Afro-Ecuadorian writers, particularly in a moment in which the debate on pluri-nationality is crucial. The main objective of Handelsman’s book is to think a pluri-national Ecuador from the Afro-Ecuadorian community’s production, and not just from the centrality as traditionally assigned to Indigenous communities. For this, the author will study different literary expressions, from the perception of the Afro subject in the works produced by the Guayaquil Group, going through the works of the most outstanding Afro-Ecuadorian writers of the 20th Century, until reaching the diverse expressions about the Afro, expressed in cultural magazines throughout the past century.